Protein and amylase profile- an aid in cultivar identification in some date palm (Phoenix dactylifera L.) cultivars (Indian Journal of Arid Horticulture, 2013)
Morphological and anatomical characteristics of performed in cold. 10 gm of leaf base material was crushed  plants have been extensively exploited in plant systematics. in ice chilled all glass pestle and mortar containing 5 ml of  However, at infra- specific level, these parameters become 0.05 M phosphate buffer, (pH 7.3). The mixture was left  limiting since varieties/ cultivars are distinguished from undisturbed for two hours at low temperature and then  each other on the basis of one or two floral or fruit centrifuged at 8000 rpm for 10 minutes. The supernatant  characters. These at times are so overlapping that it becomes was collected in a separate tube and supplemented with dry  difficult to identify the cultivars. In a situation such as this, sucrose (about 10% by volume). The extract thus obtained,  when traditional methods of taxonomy becomes limiting for was utilized subsequently for analysis.
Keywords: electrophoresis; Polymerization; foliarprotein